A porous high entropy boride ceramic material and its preparation method and application

Through the simplified boron thermal reduction and electric field sintering process, the problems of small component space and low compression strength in the preparation of porous high-entropy boronide ceramic materials are solved, and an efficient and low-cost preparation method is realized, which is suitable for the field of high-temperature thermal protection.

CN117105687BActive Publication Date: 2025-04-29SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310953557.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-04-29
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The existing porous high entropy boric ceramic materials have problems such as small component space, low compression strength, long preparation cycle, low efficiency and high production cost, which limits their application in the field of high temperature thermal protection.

Method used

Porous high entropy boronide ceramic material was prepared by mixing and grinding the metal oxide powder and pressing it into a green body and then undergoing boron thermal reduction reaction and electric field sintering in a graphite felt. This method simplifies the process flow, shortens reaction time, and reduces production costs.

Benefits of technology

The preparation of porous high-entropy boronide ceramic materials with large component space has high compression strength and low thermal conductivity. It is suitable for use in the field of high-temperature thermal protection, and has a simple process and low cost, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117105687B_ABST
    Figure CN117105687B_ABST
Patent Text Reader

Abstract

The present invention discloses a porous high-entropy boride ceramic material and its preparation method and application. The preparation method of the porous high-entropy boride ceramic material of the present invention comprises the following steps: 1) metal oxide powder and boron powder are made into a mixed powder; 2) the mixed powder is pressed into a green body and then subjected to a boron thermal reduction reaction, and then the obtained clinker is taken out for grinding and sieving to obtain a clinker powder containing a plurality of boride solid solutions; 3) the clinker powder is pressed into a clinker body and then subjected to electric field sintering to obtain a porous high-entropy boride ceramic material. The porous high-entropy boride ceramic material of the present invention has the advantages of large component space, high compression strength, low thermal conductivity, etc., and its preparation method has the advantages of simple operation, extremely short reaction time, low equipment requirements, simple process flow, low synthesis cost, etc., and is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a porous high-entropy boride ceramic material and a preparation method and application thereof. Background Art

[0002] High entropy boride ceramics are a type of ultra-high temperature ceramics with high hardness, high melting point, high modulus, and excellent antioxidant properties. They also have strong electron-phonon scattering and thermal conductivity much lower than that of single-component boride ceramics. They have broad application prospects in aerospace, refractory materials, high-temperature thermal protection and other fields.

[0003] Porous high-entropy boride ceramics (porous ceramic materials made by introducing pores into high-entropy boride ceramics) are a new type of ultra-high temperature thermal insulation material. They not only have the characteristics of light weight, low thermal conductivity and high stability of traditional porous borides, but also have a huge adjustable space for performance, and have the potential to be used in ultra-high temperature thermal protection systems. However, existing porous high-entropy boride ceramics (for example: Chen Heng et al. used a process combining carbon-boron thermal reduction with solid solution reaction and sintering to prepare a five-element porous high-entropy boride ceramic with a porosity of 75.67% and a room temperature thermal conductivity of 0.51 W·m -1 ·K -1 , compressive strength of 3.93MPa) has problems such as small component space (high-entropy boride ceramics with a component number ≥ 6 are difficult to synthesize) and low compressive strength. In addition, the preparation cycle is long (the entire preparation process takes at least 20 hours), the efficiency is low, and the production cost is high, which greatly limits its practical application.

[0004] Therefore, it is of great significance to develop a porous high-entropy boride ceramic material with large component space, high strength, low thermal conductivity, simple preparation and low cost. Summary of the invention

[0005] The object of the present invention is to provide a porous high-entropy boride ceramic material and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing a porous high entropy boride ceramic material comprises the following steps:

[0008] 1) mixing and grinding metal oxide powder and boron powder, wherein the metal oxide powder consists of at least five of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder, to obtain a mixed powder;

[0009] 2) pressing the mixed powder into a green body, embedding the green body into a graphite felt, placing the green body in a protective atmosphere, electrifying the graphite felt to cause the green body to undergo a boron thermal reduction reaction, and then taking out the obtained clinker, grinding and sieving it to obtain a clinker powder containing a plurality of boride solid solutions;

[0010] 3) The clinker powder is pressed into a clinker body, and then the clinker body is embedded in graphite felt, and then the graphite felt is electrified in a protective atmosphere to perform electric field sintering on the clinker body, thereby obtaining a porous high entropy boride ceramic material.

[0011] Preferably, the metal oxide powder in step 1) is composed of at least five of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder in equal molar ratios of metal elements.

[0012] Preferably, in step 1), the ratio of the total molar amount of metal atoms in the metal oxide powder to the molar amount of boron powder is 1:4.4-5.4.

[0013] Preferably, in step 1), the particle sizes of the HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder are all 1 μm to 3 μm, and the purity is ≥99.9%.

[0014] Preferably, the boron powder in step 1) has a particle size of 1 μm to 3 μm and a purity of ≥ 99.0%.

[0015] Preferably, the pressing in step 2) is carried out at a pressure of 8 MPa to 12 MPa, and the holding time is 3 min to 5 min.

[0016] Preferably, the green body in step 2) is in the shape of a disc with a diameter of ≤16 mm and a thickness of ≤3.5 mm.

[0017] Preferably, the size of the graphite felt in step 2) is 100 mm to 120 mm in length, 16 mm to 20 mm in width, and 4.75 mm to 6.5 mm in thickness.

[0018] Preferably, the protective atmosphere in step 2) is an argon atmosphere.

[0019] Preferably, the specific operation of the boron thermal reduction reaction in step 2) is: connect the two ends of the graphite felt to an alternating current, increase the current from 0 to 35A to 45A at a rate of 2A / s to 4A / s, and then maintain it for 50s to 70s. By performing the boron thermal reduction reaction at a relatively low current, the raw material can be made into a clinker containing a variety of boride solid solutions and pore structures of various sizes.

[0020] Preferably, in step 2), the two sides of the green body are bonded to graphite paper coated with hexagonal boron nitride before the boron thermal reduction reaction is performed. Bonding the graphite paper coated with hexagonal boron nitride can prevent the green body from reacting with the graphite paper and the graphite felt.

[0021] Preferably, the sieving in step 2) uses a nylon screen with a mesh size of 100 to 300. Grinding and sieving can destroy the macroporous skeleton, and finally obtain a clinker powder with a uniform microporous structure.

[0022] Preferably, the pressing in step 3) is carried out at a pressure of 6 MPa to 10 MPa, and the holding time is 2 min to 4 min.

[0023] Preferably, the clinker body in step 3) is in the shape of a disc with a diameter of ≤16 mm and a thickness of ≤2 mm.

[0024] Preferably, the size of the graphite felt in step 3) is 100 mm to 120 mm in length, 16 mm to 20 mm in width, and 4.75 mm to 6.5 mm in thickness.

[0025] Preferably, the protective atmosphere in step 3) is an argon atmosphere.

[0026] Preferably, the specific operation of the electric field sintering in step 3) is: connect the two ends of the graphite felt to alternating current, then increase the current from 0 to 45A to 55A within 25s to 35s, then increase the current to 65A to 75A within 15s to 25s, then maintain for 15s to 25s, and then reduce the current to 0 at a rate of 8A / s to 12A / s. By sintering at a relatively high current, the clinker containing multiple boride solid solutions can form a porous high-entropy boride ceramic material with a uniform small pore structure based on the principle of solid solution reaction sintering.

[0027] Preferably, in step 3), the two sides of the clinker blank are attached to graphite paper coated with hexagonal boron nitride before electric field sintering. Attaching the graphite paper coated with hexagonal boron nitride can prevent the clinker blank from reacting with the graphite paper and graphite felt.

[0028] A porous high-entropy boride ceramic material is made by the above preparation method.

[0029] A heat protection material comprises the porous high entropy boride ceramic material.

[0030] The beneficial effects of the present invention are as follows: the porous high-entropy boride ceramic material of the present invention has the advantages of large component space, high compression strength, low thermal conductivity, etc., and its preparation method has the advantages of simple operation, extremely short reaction time, low equipment requirements, simple process flow, low synthesis cost, etc., and is suitable for large-scale industrial production.

[0031] Specifically:

[0032] 1) The present invention uses cheap transition metal oxide powder and boron powder as raw materials, and prepares a porous high-entropy boride ceramic material with any five or more element components of Hf, Zr, Ti, Ta, Nb, Cr, Mo, V and W through a two-step rapid reaction method. The element composition of the porous high-entropy boride ceramic material can be adjusted in a very large space, which overcomes the problem that the traditional method cannot prepare a porous high-entropy boride ceramic material with a huge component space;

[0033] 2) The metal elements in the porous high entropy boride ceramic material of the present invention are evenly distributed, with about 50% of medium pores, concentrated pore size distribution (0.1 μm to 1.2 μm), and a small average pore size (about 0.53 μm);

[0034] 3) The porous high entropy boride ceramic material of the present invention has high compressive strength (up to 282MPa) and low thermal conductivity (the lowest is only 0.76W·m -1 ·K -1 ), which is significantly better than the existing porous high entropy borides (compressive strength of about 3.93MPa, thermal conductivity of about 0.51W·m -1 ·K -1 ), suitable for application in the field of high temperature thermal protection;

[0035] 4) The preparation method of the porous high-entropy boride ceramic material of the present invention has the advantages of short reaction time (less than 5 minutes), low equipment requirements, simple process flow, low synthesis cost, etc. The porous high-entropy boride ceramic has high synthesis efficiency and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 : This is the XRD diagram of the clinker powder in Examples 1 to 3.

[0037] Figure 2 1 is the XRD diagram of the porous high entropy boride ceramic material of Examples 1 to 3.

[0038] Figure 3 The SEM image and EDS element surface distribution map of the porous high entropy boride ceramic material of Example 3.

[0039] Figure 4 This is the pore size distribution diagram of the porous high entropy boride ceramic material of Example 3.

[0040] Figure 5 This is the stress-strain curve of the porous high entropy boride ceramic material of Example 3 during the compression process.

[0041] Figure 6 This is a graph showing the thermal conductivity test results of the porous high entropy boride ceramic material of Example 3 at different temperatures. DETAILED DESCRIPTION

[0042] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0043] The particle sizes of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder in Examples 1 to 3 are all 1 μm to 3 μm, and the purity is ≥99.9%.

[0044] The particle size of the boron powder in Examples 1 to 3 is 1 μm to 3 μm, and the purity is ≥ 99.0%.

[0045] Embodiment 1:

[0046] A porous high entropy boride ceramic material, the preparation method of which comprises the following steps:

[0047] 1) Add 0.73 g of HfO2 powder, 0.43 g of ZrO2 powder, 0.28 g of TiO2 powder, 0.77 g of Ta2O5 powder, 0.46 g of Nb2O5 powder and 0.89 g of boron powder into an agate mortar and grind manually for 60 min to obtain a mixed powder;

[0048] 2) 1.5 g of the mixed powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 8 MPa, and the pressure was maintained for 3 min to obtain a green body (thickness of about 3.5 mm);

[0049] 3) A through hole of about 22 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness. Then, graphite paper coated with hexagonal boron nitride of the same size was pasted on both sides of the green body and inserted into the through hole of the graphite felt. Then, electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reaction chamber. The reaction chamber was sealed. The reaction chamber was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 -3 Pa, then slowly introduce argon to normal pressure, turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 35A at a rate of 2A / s, and then keep it for 50s, turn off the power switch and cool it naturally, then take out the obtained clinker, grind it and pass it through a 100-mesh nylon sieve, take the powder under the sieve, and obtain the clinker powder containing multiple boride solid solutions (recorded as 5HEB-S1);

[0050] 4) 1.2 g of clinker powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 6 MPa, and the pressure was maintained for 2 min to obtain a clinker body (thickness of about 2 mm);

[0051] 5) A through hole of about 22 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness. Then, graphite paper coated with hexagonal boron nitride of the same size was pasted on both sides of the clinker body and inserted into the through hole of the graphite felt. Then, electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reaction chamber. The reaction chamber was sealed. The reaction chamber was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 -3 Pa, and then slowly introduce argon gas to normal pressure, and then turn on the power switch to connect the two ends of the graphite felt to AC, and then increase the current from 0 to 45A within 25s, and then increase the current to 65A within 15s, and then keep it for 15s, and then reduce the current to 0 at a rate of 8A / s, and then turn off the power switch and cool it naturally to obtain a porous high entropy boride ceramic material (five-element porous high entropy boride (Hf 1 / 5 Zr 1 / 5Ta 1 / 5 Nb 1 / 5 Ti 1 / 5 )B2, recorded as 5HEB).

[0052] Performance Test:

[0053] The X-ray diffraction (XRD) pattern of the clinker powder in this embodiment is as follows: Figure 1 As shown, the XRD pattern of the porous high entropy boride ceramic material of this embodiment is as follows Figure 2 shown.

[0054] Depend on Figure 1 It can be seen that the clinker powder 5HEB-S1 in this embodiment contains a variety of boride solid solution phases.

[0055] Depend on Figure 2 It can be seen that the porous high entropy boride ceramic material 5HEB of this embodiment is a pure phase and does not contain other impurity phases.

[0056] After testing (the testing method is the same as that of Example 3), the five constituent elements Hf, Zr, Ta, Nb and Ti in the porous high entropy boride ceramic material 5HEB of this embodiment are evenly distributed without obvious segregation, the pore size distribution range is 0.2μm to 1.2μm, the porosity is about 48%, the compressive strength is 262MPa, and the thermal conductivity at room temperature is 0.95W·m -1 ·K -1 .

[0057] Embodiment 2:

[0058] A porous high entropy boride ceramic material, the preparation method of which comprises the following steps:

[0059] 1) Add 0.47 g of HfO2 powder, 0.28 g of ZrO2 powder, 0.18 g of TiO2 powder, 0.50 g of Ta2O5 powder, 0.30 g of Nb2O5 powder, 0.17 g of Cr2O3 powder, 0.32 g of MoO3 powder and 0.76 g of boron powder into an agate mortar and grind manually for 60 min to obtain a mixed powder;

[0060] 2) 1.5 g of the mixed powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 10 MPa, and the pressure was maintained for 4 min to obtain a green body (thickness of about 3.5 mm);

[0061] 3) A through hole of about 22 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 110 mm in length, 18 mm in width and 4.75 mm in thickness. Then, graphite paper coated with hexagonal boron nitride of the same size was pasted on both sides of the green body and inserted into the through hole of the graphite felt. Then, electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reaction chamber. The reaction chamber was sealed. The reaction chamber was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 -3 Pa, then slowly introduce argon to normal pressure, turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 40A at a rate of 3A / s, and then keep it for 60s, turn off the power switch and cool it naturally, then take out the obtained clinker, grind it and pass it through a 100-mesh nylon sieve, take the powder under the sieve, and obtain the clinker powder containing multiple boride solid solutions (recorded as 7HEB-S1);

[0062] 4) 1.2 g of clinker powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 8 MPa, and the pressure was maintained for 3 min to obtain a clinker body (about 2 mm thick);

[0063] 5) A through hole of about 22 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 110 mm in length, 18 mm in width and 4.75 mm in thickness. Then, graphite paper of the same size coated with hexagonal boron nitride was pasted on both sides of the clinker body and inserted into the through hole of the graphite felt. Then, electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reaction chamber. The reaction chamber was sealed. The reaction chamber was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 -3 Pa, and then slowly introduce argon to normal pressure, then turn on the power switch to connect the two ends of the graphite felt to AC, then increase the current from 0 to 50A within 30s, then increase the current to 70A within 20s, and then keep it for 20s, then reduce the current to 0 at a rate of 10A / s, and then turn off the power switch and cool naturally to obtain a porous high entropy boride ceramic material (seven-element porous high entropy boride (Hf 1 / 7 Zr 1 / 7Ta 1 / 7 Nb 1 / 7 Ti 1 / 7 Cr 1 / 7 Mo 1 / 7 )B2, recorded as 7HEB).

[0064] Performance Test:

[0065] The XRD pattern of the clinker powder in this embodiment is as follows Figure 1 As shown, the XRD pattern of the porous high entropy boride ceramic material of this embodiment is as follows Figure 2 shown.

[0066] Depend on Figure 1 It can be seen that the clinker powder 7HEB-S1 in this embodiment contains a variety of boride solid solution phases.

[0067] Depend on Figure 2 It can be seen that the porous high entropy boride ceramic material 7HEB of this embodiment is a pure phase and does not contain other impurity phases.

[0068] After testing (the testing method is the same as that of Example 3), the seven constituent elements of Hf, Zr, Ti, Ta, Nb, Cr and Mo in the porous high entropy boride ceramic material 7HEB of this embodiment are evenly distributed without obvious segregation, the pore size distribution range is 0.2μm to 1.0μm, the porosity is about 54%, the compressive strength is 274MPa, and the thermal conductivity at room temperature is 0.83W·m -1 ·K -1 .

[0069] Embodiment 3:

[0070] A porous high entropy boride ceramic material, the preparation method of which comprises the following steps:

[0071] 1) Add 0.36 g of HfO2 powder, 0.21 g of ZrO2 powder, 0.14 g of TiO2 powder, 0.38 g of Ta2O5 powder, 0.23 g of Nb2O5 powder, 0.13 g of Cr2O3 powder, 0.25 g of MoO3 powder, 0.16 g of V2O5 powder, 0.40 g of WO3 powder and 0.77 g of boron powder into an agate mortar and grind by hand for 60 min to obtain a mixed powder;

[0072] 2) 1.5 g of the mixed powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 12 MPa, and the pressure was maintained for 5 min to obtain a green body (thickness of about 3.5 mm);

[0073] 3) A through hole of about 22 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G650) with a size of 120 mm in length, 20 mm in width and 6.5 mm in thickness. Then, graphite paper coated with hexagonal boron nitride of the same size was pasted on both sides of the green body and inserted into the through hole of the graphite felt. Then, electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reaction chamber. The reaction chamber was sealed. The reaction chamber was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 -3 Pa, then slowly introduce argon to normal pressure, turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 45A at a rate of 4A / s, and then keep it for 70s, turn off the power switch and cool it naturally, then take out the obtained clinker, grind it and pass it through a 100-mesh nylon sieve, take the powder under the sieve, and obtain the clinker powder containing multiple boride solid solutions (recorded as 9HEB-S1);

[0074] 4) 1.2 g of clinker powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 10 MPa, and the pressure was maintained for 4 min to obtain a clinker body (thickness of about 2 mm);

[0075] 5) A through hole of about 22 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G650) with a size of 120 mm in length, 20 mm in width and 6.5 mm in thickness. Then, graphite paper coated with hexagonal boron nitride of the same size was pasted on both sides of the clinker body and inserted into the through hole of the graphite felt. Then, electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reaction chamber. The reaction chamber was sealed. The reaction chamber was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 -3 Pa, and then slowly introduce argon gas to normal pressure, then turn on the power switch to connect the two ends of the graphite felt to AC, then increase the current from 0 to 55A within 35s, then increase the current to 75A within 25s, and then maintain it for 25s, then reduce the current to 0 at a rate of 12A / s, and then turn off the power switch and cool it naturally to obtain a porous high entropy boride ceramic material (nine-element porous high entropy boride (Hf 1 / 9 Zr 1 / 9Ta 1 / 9 Nb 1 / 9 Ti 1 / 9 Cr 1 / 9 Mo 1 / 9 V 1 / 9 W 1 / 9 )B2, recorded as 9HEB).

[0076] Performance Test:

[0077] 1) The XRD pattern of the clinker powder in this embodiment is as follows Figure 1 As shown, the XRD pattern of the porous high entropy boride ceramic material of this embodiment is as follows Figure 2 shown.

[0078] Depend on Figure 1 It can be seen that the clinker powder 9HEB-S1 in this embodiment contains a variety of boride solid solution phases.

[0079] Depend on Figure 2 It can be seen that the porous high entropy boride ceramic material 9HEB of this embodiment is a pure phase and does not contain other impurity phases.

[0080] 2) The scanning electron microscope (SEM) image and EDS element surface distribution map of the porous high entropy boride ceramic material of this embodiment are as follows: Figure 3 The pore size distribution diagram is shown in Figure 4 The stress-strain curve during compression is shown in Figure 5 As shown in the figure, the thermal conductivity test results at different temperatures are as follows Figure 6 shown.

[0081] Depend on Figure 3It can be seen that the nine constituent elements Hf, Zr, Ti, Ta, Nb, Cr, Mo, V and W in the porous high-entropy boride ceramic material 9HEB of this embodiment are evenly distributed without obvious segregation.

[0082] Depend on Figure 4 It can be seen that the pore size distribution range of the porous high entropy boride ceramic material 9HEB of this embodiment is 0.1 μm to 1.0 μm, and the porosity is about 50%.

[0083] Depend on Figure 5 It can be seen that the porous high entropy boride ceramic material 9HEB of this embodiment has a compressive strength of up to 282 MPa.

[0084] Depend on Figure 6 It can be seen that the porous high entropy boride ceramic material 9HEB of this embodiment has a low thermal conductivity at room temperature, which is 0.76 W·m -1 ·K -1 .

[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a porous high entropy boride ceramic material, characterized in that: The following steps are involved: 1) mixing and grinding metal oxide powder and boron powder, wherein the metal oxide powder consists of at least five of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder, to obtain a mixed powder; 2) Pressing the mixed powder into a green body, embedding the green body into graphite felt, and then applying electricity to the graphite felt in a protective atmosphere to cause the green body to undergo a boron thermal reduction reaction, and then taking out the obtained clinker, grinding and sieving it to obtain a clinker powder containing a plurality of boride solid solutions; 3) Pressing the clinker powder into a clinker body, then embedding the clinker body into graphite felt, and then placing the graphite felt in a protective atmosphere to conduct electric field sintering on the clinker body, thereby obtaining a porous high entropy boride ceramic material; Step 2) The specific operation of the boron thermal reduction reaction is: connect the two ends of the graphite felt to an alternating current, increase the current from 0 to 35A to 45A at a rate of 2A / s to 4A / s, and then maintain it for 50s to 70s; Step 3) The specific operation of the electric field sintering is: connect the two ends of the graphite felt to alternating current, then increase the current from 0 to 45A-55A within 25s-35s, then increase the current to 65A-75A within 15s-25s, then maintain for 15s-25s, and then reduce the current to 0 at a rate of 8A / s-12A / s.

2. The preparation method according to claim 1, characterized in that: Step 1) The metal oxide powder is composed of at least five of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder in equal molar ratios of metal elements; Step 1) The ratio of the total molar amount of metal atoms in the metal oxide powder to the molar amount of boron powder is 1:4.4-5.4; Step 1) The particle sizes of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder are all 1μm-3μm, and the purity is ≥99.9%; Step 1) The particle size of the boron powder is 1μm-3μm, and the purity is ≥99.0%.

3. The preparation method according to claim 1, characterized in that: Step 2) The pressing is carried out at a pressure of 8 MPa to 12 MPa, and the pressure holding time is 3 min to 5 min.

4. The preparation method according to claim 1 or 3, characterized in that: Step 2) The green body is in the shape of a disc, with a diameter of ≤16 mm and a thickness of ≤3.5 mm; Step 2) The size of the graphite felt is 100 mm to 120 mm in length, 16 mm to 20 mm in width, and 4.75 mm to 6.5 mm in thickness.

5. The preparation method according to claim 1, characterized in that: Step 3) The pressing is carried out at a pressure of 6 MPa to 10 MPa, and the holding time is 2 min to 4 min.

6. The preparation method according to claim 1 or 5, characterized in that: Step 3) The clinker body is in the shape of a disc, with a diameter of ≤16mm and a thickness of ≤2mm; Step 3) The size of the graphite felt is 100mm-120mm in length, 16mm-20mm in width, and 4.75mm-6.5mm in thickness.

7. A porous high entropy boride ceramic material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. A heat protection material, characterized in that: The porous high entropy boride ceramic material comprises the porous high entropy boride ceramic material according to claim 7.

Citation Information

Patent Citations

  • Porous high-entropy hexaboride ceramic and preparation method thereof

    CN110615681A

  • High-entropy boride ceramic powder as well as preparation method and application thereof

    CN115196968A